Nature's Civil War : Common Soldiers and the Environment in 1862 Virginia - Meier, Kathryn Shively (Book collections on Project MUSE., 2013)
Using soldiers' letters, diaries and memoirs, plus a wealth of additional personal accounts, medical sources, newspapers and government documents, Meier reveals how soldiers strove to maintain their physical and mental health by combating their deadliest enemy - nature.